Shedding Light on the Taxonomic Diversity of the South American Miocene Caimans: The Status of Melanosuchus fisheri (Crocodylia, Alligatoroidea) - Bona, Paula (2017)
Fil: Bona, Paula. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina